Effect of plant secondary metabolites on feeding behavior of microtine and arvicoline rodent species - Hansen, Sabine; Stolter, Caroline; Jacob, Jens (Journal of Pest Science, 2016)
Rodents are among the most damaging pests in agriculture worldwide. High-density populations of rodent pests can kill plants or diminish their growth, and reduce both fruit size and the number of seeds. Therefore, rodent pests can lead to considerable crop loss and require management actions to minimize damage. Optimal management of pest rodents is usually based on the combination of methods to reduce damage. Although rodenticides are usually the most commonly deployed approach, they have undesirable side effects. Consequently, more environmentally benign approaches such as repellents or attractants to lure rodents away from fields are gaining traction. The dispersal of a large number of juvenile males at certain times of year has prompted us to focus on male rodents for our experiments. We used laboratory feeding experiments to measure how the odor of plant secondary metabolites (PSMs) affects two pest rodents: common voles (Microtus arvalis, Pallas) and house mice (Mus musculus, L.). We tested eighteen different PSMs or combinations thereof with voles. Four PSMs reduced feeding and seven PSMs increased feeding of male common voles. Five of six tested odors were effective as repellents against house mice. However, we assume a species-specific response to volatile PSMs repellents. This study demonstrated that four repellents reduced feeding in both rodent species. Our results contribute to the development of non-lethal management tools for rodent pest species that are potentially more suitable than traps and rodenticides. This approach could be applicable to a variety of crops if effective at field conditions.